Aficamten for Symptomatic Obstructive Hypertrophic Cardiomyopathy - Maron, Martin S; Masri, Ahmad; Nassif, Michael E; Barriales-Villa, Roberto; Arad, Michael; Cardim, Nuno; Choudhury, Lubna; Claggett, Brian; Coats, Caroline J; Düngen, Hans-Dirk; Garcia-Pavia, Pablo; Hagège, Albert A; et al. (The New England journal of medicine, 2024)
BACKGROUND: One of the major determinants of exercise intolerance and limiting symptoms among patients with obstructive hypertrophic cardiomyopathy (HCM) is an elevated intracardiac pressure resulting from left ventricular outflow tract obstruction. Aficamten is an oral selective cardiac myosin inhibitor that reduces left ventricular outflow tract gradients by mitigating cardiac hypercontractility. METHODS: In this phase 3, double-blind trial, we randomly assigned adults with symptomatic obstructive HCM to receive aficamten (starting dose, 5 mg; maximum dose, 20 mg) or placebo for 24 weeks, with dose adjustment based on echocardiography results. The primary end point was the change from baseline to week 24 in the peak oxygen uptake as assessed by cardiopulmonary exercise testing. The 10 prespecified secondary end points (tested hierarchically) were change in the Kansas City Cardiomyopathy Questionnaire clinical summary score (KCCQ-CSS), improvement in the New York Heart Association (NYHA) functional class, change in the pressure gradient after the Valsalva maneuver, occurrence of a gradient of less than 30 mm Hg after the Valsalva maneuver, and duration of eligibility for septal reduction therapy (all assessed at week 24); change in the KCCQ-CSS, improvement in the NYHA functional class, change in the pressure gradient after the Valsalva maneuver, and occurrence of a gradient of less than 30 mm Hg after the Valsalva maneuver (all assessed at week 12); and change in the total workload as assessed by cardiopulmonary exercise testing at week 24. RESULTS: A total of 282 patients underwent randomization: 142 to the aficamten group and 140 to the placebo group. The mean age was 59.1 years, 59.2% were men, the baseline mean resting left ventricular outflow tract gradient was 55.1 mm Hg, and the baseline mean left ventricular ejection fraction was 74.8%. At 24 weeks, the mean change in the peak oxygen uptake was 1.8 ml per kilogram per minute (95% confidence interval [CI], 1.2 to 2.3) in the aficamten group and 0.0 ml per kilogram per minute (95% CI, -0.5 to 0.5) in the placebo group (least-squares mean between-group difference, 1.7 ml per kilogram per minute; 95% CI, 1.0 to 2.4; P<0.001). The results for all 10 secondary end points were significantly improved with aficamten as compared with placebo. The incidence of adverse events appeared to be similar in the two groups. CONCLUSIONS: Among patients with symptomatic obstructive HCM, treatment with aficamten resulted in a significantly greater improvement in peak oxygen uptake than placebo. (Funded by Cytokinetics; SEQUOIA-HCM ClinicalTrials.gov number, NCT05186818.).
Keywords: Valsalva Maneuver; Cardiomyopathy, Hypertrophic; senioři; srdeční myosiny; Aged; dvojitá slepá metoda; Valsalvův manévr; benzylaminy; Male; Double-Blind Method; kontrakce myokardu; uracil; lidé; Cardiovascular Agents; lidé středního věku; Humans; Cardiac Myosins; Exercise Tolerance; Middle Aged; Exercise Test; spotřeba kyslíku; Ventricular Outflow Obstruction; Myocardial Contraction; kardiovaskulární látky; mužské pohlaví; Oxygen Consumption; Administration, Oral; tolerance zátěže; hypertrofická kardiomyopatie; ženské pohlaví; obstrukce výtoku ze srdeční komory; Uracil; Female; aplikace orální; zátěžový test; Benzylamines